(untitled) (Scientia Agricola, 2021)
Sanitization using chemical agents to reduce the microbiological load on the surface of agricultural products have the drawback of leaving residues. Conversely, physical treatments, such as ultraviolet radiation C (UV-C), are residue-free, non-toxic and environmentally friendly. Ripe figs are perishable, exhibiting an epidermis with low resistance to mechanical treatment, high water content and the ostiole, which is an open door that expedites undesirable microorganism penetration. In this study, the effect of different energy levels of UV-C radiation on the appearance and physico-chemical properties of the figs when stored at 10 °C and 20 °C was evaluated focusing on the technological parameters of the application of radiation. The energy levels of radiation applied were 0.00, 0.71, 1.32, 2.64 and 4.01 kJ m–2 and they showed neither acceleration nor delay effects on fig ripening. Figs exposed to the radiation energy at 0.71, 1.32, 2.64 and 4.01 kJ m–2 showed a lower incidence of rot at the same temperature, but the figs exposed to the highest radiation, 4.01 kJ m–2, showed more wilting and stains, which significantly impaired their appearance. UV-C radiation reduces the development of rotting, providing evidence of its potential in the postharvest processing of ripe figs. However, radiation levels should be limited to avoid undesirable epidermis stains.